Peripheral narratives and urban ethnographies: the everyday perspective of subjects on urban experiences - Santos, Karina Malachias Domingos dos [UNESP]; Whitacker, Arthur Magon [UNESP] (Revista Brasileira de Estudos Urbanos e Regionais (RBEUR), 2025)
We have drawn on elements of urban ethnography and action research to examine socio-spatial practices and urban experiences from a peripheral perspective. The study, conducted in the districts of Cidade Tiradentes and São Mateus, in the city of São Paulo, evaluated the urban routes and narratives of residents who, associated with the researcher's experiences, have exposed a unique, fractured peripheral condition that reveals socio-spatial fragmentation.